2009
DOI: 10.1007/s00268-009-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Experience Training Non‐Physician Anesthesia Providers in Haiti

Abstract: Surgery is increasingly recognized as an effective means of treating a proportion of the global burden of disease, especially in resource‐limited countries. Often non‐physicians, such as nurses, provide the majority of anesthesia; however, their training and formal supervision is often of low priority or even non‐existent. To increase the number of safe anesthesia providers in Haiti, Médecins Sans Frontières has trained nurse anesthetists (NAs) for over 10 years. This article describes the challenges, outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…4 On their medical experience in Haiti from 1998 to 2008, Rosseel et al 9 reported that working conditions are suboptimal, with frequent shortage of equipment, oxygen, anesthetics, and other medications. For the last 16 years, the Physicians for Humanity-Haiti team has worked to provide surgical and medical attention to Haitians in need and has played an active role in the development of regional medical infrastructure.…”
Section: Discussionmentioning
confidence: 98%
“…4 On their medical experience in Haiti from 1998 to 2008, Rosseel et al 9 reported that working conditions are suboptimal, with frequent shortage of equipment, oxygen, anesthetics, and other medications. For the last 16 years, the Physicians for Humanity-Haiti team has worked to provide surgical and medical attention to Haitians in need and has played an active role in the development of regional medical infrastructure.…”
Section: Discussionmentioning
confidence: 98%
“…With only 35 anesthetists practicing in Haiti (of whom few work outside Port-au-Prince), planned surgical interventions were often canceled the same day because of a lack of personnel or anesthesia equipment (and particularly a lack of oxygen). 14 The decision to perform major surgical intervention necessitating tracheotomy was carefully considered because of the lack of an aspiration system in the hospital and the absence of paramedical personnel for patient monitoring. The 6-bed ENT hospital area was common to children and adults, men, and women, and did not have any dedicated paramedical personnel (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Study on anaesthesia services in one of the African countries showed that the majority of anaesthesia procedures were administered by non-physicians. Even the anesthesiologist was not involved in pain as well as emergency services 710. The other survey further highlighted that there was serious crunch in the entire anaesthesia services.…”
Section: Magnitude Of Problem and Solutionmentioning
confidence: 99%
“…But these services are not available to majority of population because of poverty, growing population, limited resources, cost of treatment, disparity and non-uniformity of available healthcare services, increasing burden of non-communicable diseases along with communicable disease and increasing needs of aging population. The need for non-physician anaesthetists cannot be overlooked particularly in areas where properly trained anaesthesiologists are lacking 10. However, standard training of these non-physicians should be ensured.…”
Section: Challenges Ahead In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation